2017
DOI: 10.1017/s0714980817000186
|View full text |Cite
|
Sign up to set email alerts
|

How’s Your Health at Home: Frail Homebound Patients Reported Health Experience and Outcomes

Abstract: RÉSUMÉPour notre sondage, nous avons utilisé une méthodologie mixte basée sur le Web (How's Your Health -Frail) pour examiner la santé des adultes fragiles (78% âgés de 80 ans et plus) inscrits à un programme de soins primaires à domicile à Vancouver, au Canada. Soixante pour cent des répondants admissibles ont participé, représentant plus d'un quart (92/350, 26,2%) de tous les individus qui reçoivent le service. Malgré des niveaux élevés de co-morbidité et de dépendance fonctionnelle, 50% ont jugé leur santé … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…[41][42][43] One article reported findings from a mixedmethods study. 44 Only 3 of the eligible articles in this review explicitly focused on primary care: these included a commentary, 37 a literature review, 30 and a mixed-methods study. 44 Among the 21 articles, 4 mentioned primary care 4,8,27,42 and 6 reported findings that were applicable to primary care settings.…”
Section: --Synthesis--mentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43] One article reported findings from a mixedmethods study. 44 Only 3 of the eligible articles in this review explicitly focused on primary care: these included a commentary, 37 a literature review, 30 and a mixed-methods study. 44 Among the 21 articles, 4 mentioned primary care 4,8,27,42 and 6 reported findings that were applicable to primary care settings.…”
Section: --Synthesis--mentioning
confidence: 99%
“…44 Only 3 of the eligible articles in this review explicitly focused on primary care: these included a commentary, 37 a literature review, 30 and a mixed-methods study. 44 Among the 21 articles, 4 mentioned primary care 4,8,27,42 and 6 reported findings that were applicable to primary care settings. 3,28,29,32,34,39 Although assessing the quality of the studies is outside the scope of this review framework, 24 it is important to note that most of the data in this review are from commentaries and survey data.…”
Section: --Synthesis--mentioning
confidence: 99%
“…The findings showed that participants, who were more satisfied with this aspect of usability, also rated their health higher. Social contact and possibility to engage in social activities is related to higher self-rated health in several previous studies [ 35 , 36 , 37 ]. Some of the participants in this study are considered as frail elderly and might have limited possibility to engage in social activities outside the home, which makes the own home and its usability more important.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, a successful SAINT must aim to serve, not just survey. Our SAINT was developed for people aged two and older and includes tools that support general problem-solving and decision-making, as well as special versions for homebound patients and those in the hospital [ 26 , 27 ]. Variations of the SAINT have also been developed to comply with different types of regulatory requirements, including those of the Center for Medicare Services and state Medicaid authorities, as detailed at https://howsyourhealth.org/static/HYHModifications.pdf .…”
Section: Characteristics Of An Effective Saintmentioning
confidence: 99%